Fracture energy based approach for cemented carbides grain debonding - Debras, Colin; Dubar, Laurent; Dubar, Mirentxu; Hubert, Cédric; Dubois, André (International journal of mechanical sciences, 2019)
•The shape of WC grains can be approximated by a rectangle with good accuracy.•WC grains with borders parallel to the surface are 100 times less sensitive to debonding than tilted grains.•Equiaxed grains are less sensitive to debonding than elongated grains.•WC grains are subject to debonding whatever their shape or orientation as soon as friction is high (Coulomb's coefficient higher than 0.4). Cemented carbide materials exhibit high hardness and fracture toughness. As a consequence they possess an excellent wear resistance that make them a material of choice for the manufacturing of cutting, drilling and forming tools. Cemented carbide materials are made of tungsten carbide (WC) grains embedded in a ductile metal phase, generally made of cobalt. The wear mechanism of the tungsten carbide and cobalt composites (WCCo) operates in several successive steps: removal of the cobalt binder in the surface vicinity, plastic deformation and/or fracture of WC grains, debonding of WC grains and finally galling of workpiece material in the cavities freed of the WC grains. The present study focuses on the debonding step of the WCCo wear mechanism. A micromechanical finite element is developed to study de sensitivity of a WC grain to be torn off the surface of a WCCo composite structure. The model considers a single WC grain embedded in a homogeneous elementary volume of WCCo material. The geometry of the WC grain is a rectangle which perimeter, width and length are based on statistical analyses of actual WCCo die surfaces used in cold forming. Cohesive elements are used to model the junction between the grain and the elementary volume. The grain is torn off the surface when the fracture energy calculated within the cohesive element is totally consumed. The loadings applied on the grain are based on actual cold heading forming sequences. Various grain size, shape, orientation and friction conditions are tested. Results show that grain orientation, friction and WCCo material toughness play a great role in WC grain removal. Equiaxed grains with small perimeter are less sensitive to debonding.